The Eastern Christian Churches: An Overview - Thonippara, Francis (Asian Horizons, 2025)
An attempt is made to introduce the Eastern Christian Churches,[1] both Catholics and non-Catholics, to readers who find it difficult to understand the differences between different churches. In seven sections the churches which are in communion with Rome and which are not in communion with Rome are introduced in a less complicated way. A basic understanding of the Eastern Churches is needed to have a more comprehensive understanding of the Christian churches spread all over the world. It is not an easy task to give a brief description about these churches as the vicissitudes of the history of each church is different from the other church. However, efforts have been made to present the brief history of each church as much comprehensible as possible. [1]In this paper I used Eastern Christian Churches or Oriental Churches interchangeably.